Association between psychotropic medications and presence of sleep bruxism: A systematic review. (3rd May 2018) - Melo, G.; Dutra, K. L.; Rodrigues Filho, R.; Ortega, A. O. L.; Porporatti, A. L.; Dick, B.; Flores‐Mir, C.; De Luca Canto, G.
Summary: The purpose of this study was to systematically review the literature for studies that investigated the association between use of psychotropic medications and presence of sleep bruxism (SB). Observational studies were selected in a two‐phase process. Searches were performed on six electronic databases, and a grey literature search was conducted on three databases. SB diagnosis was based on questionnaires or clinical examinations; no polysomnography examinations were performed. Risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Analytical Cross‐Sectional Studies. Overall quality of evidence was evaluated according to the Grading of Recommendations Assessment, Development and Evaluation criteria. Five analytical cross‐sectional studies were included, evaluating antidepressants, anticonvulsants and psychostimulants. One study was judged as low risk of bias, three as moderate risk and one high risk. Antidepressants were evaluated in adult populations only; duloxetine (Odds Ratio [OR] = 2.16; 95% Confidence Interval [95% CI] = 1.12‐4.17), paroxetine (OR = 3.63; 95% CI = 2.15‐6.13) and venlafaxine (OR = 2.28; 95% CI = 1.34‐3.86) were positively associated with SB risk. No increased odds of SB were observed considering use of citalopram, escitalopram, fluoxetine, mirtazapine and sertraline. With regard to anticonvulsants, only barbiturates were associated with SB in children (OR = 14.70; 95% CI = 1.85‐116.90), while no increased odds were observed for benzodiazepine, carbamazepine and valproate. The only psychostimulant evaluated was methylphenidate, and an association with SB was observed in adolescents (OR = 1.67; 95% CI = 1.03‐2.68). Findings from this SR suggested that medications such as duloxetine, paroxetine, venlafaxine, barbiturates and methylphenidate might be associated with SB; however, overall quality of evidence was considered very low, and therefore, caution is recommended.